Enabling agency through participatory action research in an honours-level postgraduate class in a school of education - Pillay, A. (South African Journal of Higher Education, 2018)
This article argues that it is feasible to use participatory action research to enable agency in a university lecture room. Underpinned by critical pedagogy, this qualitative study, shaped by a critical paradigm, used three cycles of planning, acting, observing and reflecting with 14 honours-level postgraduate students. After each cycle, data generating methods, including written opinion pieces, open-ended questionnaires, and short written tasks, were used to ascertain the effectiveness of various interventions in facilitating the teachers’ understanding and/or enactment of agency. Findings included, firstly, that explicit teaching about the concept ’agency’ is required for full understanding of the concept. Secondly, while participants engaged with the complexities of agency, they displayed increasing independence of thought and confidence in written and oral work. Finally, they understood the need for life-long learning and regular reflection on their professional identities.